YOUTH AS TRUTH-TELLERS AND RIGHTS-HOLDERS: LEGAL AND INSTITUTIONAL REFORMS TO ENABLE YOUTH HOUSING SECURITY - Nichols, Naomi; Malenfant, Jayne (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
In the first pan-Canadian study on youth homelessness, 57.8% of youth reported prior involvement with child protection services. Indeed, transitions from government institutions (e.g., child/youth protection, inpatient mental health treatment, the youth justice system) represent common pathways into homelessness for youth across North America. This article examines young people’s experiences navigating youth protection services to identify institutional, legislative, and policy processes that pose problems for youth experiencing or at risk of homelessness, as well as processes that show promise for the promotion of the interests, protection, and well-being of youth. Our participatory youth research team explored homeless youth’s histories of involvement with youth protection services, seeking to clarify the sociolegal mechanisms in and beyond the youth protection system that make young people vulnerable to homelessness. Youth and adult co-researchers interviewed 38 individual youth (aged 16–29) who completed 64 qualitative institutional history interviews. According to our analysis, young people identified the following sociolegal practices as implicated in their experiences of homelessness: the use of totalizing institutions, the criminalization of runaways, the abrupt cessation of service delivery at 18 years of age, a systemic failure to view youth as rights-holders, and an overly complex emancipation process.